Internet of behaviors implementation in organizational contexts - Russo, Nelson; Reis, Leonilde; Silveira, Clara; Carvalho, Luisa Cagica (IGI Global, 2023)
"Internet of behaviors (IoB), also known as the internet of behavior, emerged as a natural consequence of the internet of things (IoT) and artificial intelligence (AI). IoB is an area of investigation that compiles three fields of study: IoT, data analysis, and behavioral science. IoB seeks to explain the data obtained from a behavioral point of view, analyzing human interaction with technology and referring to the process by which user-controlled data is evaluated from a behavioral psychology perspective.Internet of Behaviors Implementation in Organizational Contexts explores internet of behaviors solutions that promote people's quality of life. This book explores and discusses, through innovative studies, case studies, systematic literature reviews, and reports. The content within this publication represents research encompassing the internet of behaviors, internet of things, big data, artificial intelligence, blockchain, smart cities, human-centric approach for digital technologies, ICT sustainability, and more. This vital reference source led by an editor with over two decades of experience is optimized for university professors, researchers, undergraduate and graduate level students, and business managers and professionals across several industries related to or utilizing the internet of things (IoT)."--
Keywords: Internet of things -- Social aspects; Internet of things -- Economic aspects; Human-computer interaction; Electronic commerce; Business -- Data processing